A Unique Subset of γδ T Cells Expands and Produces IL-10 in Patients with Naturally Acquired Immunity against Falciparum Malaria - Taniguchi, Tomoyo; Md Mannoor, Kaiissar; Nonaka, Daisuke; Toma, Hiromu; Li, Changchun; Narita, Miwako; Vanisaveth, Viengxay; Kano, Shigeyuki; Takahashi, Masuhiro; Watanabe, Hisami (Frontiers in Microbiology, 2017)
Although expansions in gamma delta T cell populations are known to occur in the peripheral blood of patients infected with Plasmodium falciparum, the role of these cells in people with naturally acquired immunity against P. falciparum who live in malaria-endemic areas is poorly understood. We used a cross-sectional survey to investigate the role of peripheral blood gamma delta T cells in people living in Lao People’s Democratic Republic, a malaria-endemic area. We found that the proportion of non-Vgamma9 gamma delta T cells was higher in non-hospitalized patients with uncomplicated falciparum malaria (UMPs) from this region. Notably, we found that the non-Vgamma9 gamma delta T cells in the peripheral blood of UMPs and negative controls from this region had the potential to expand and produce IL-10 and interferon-gamma when cultured in the presence of IL-2 and/or crude P. falciparum antigens for 10 days. Furthermore, these cells were associated with plasma interleukin 10 (IL-10), which was elevated in UMPs. This is the first report demonstrating that, in UMPs living in a malaria-endemic area, a gamma delta T cell subset, the non-Vgamma9 gamma delta T cells, expands and produces IL-10. These results contribute to understanding of the mechanisms of naturally acquired immunity against P. falciparum.